Pengaruh Literasi Investasi, Persepsi Risiko, dan Pengaruh Influencer di Media Sosial terhadap Minat Investasi (Studi Kasus Mahasiswa Universitas Islam Malang) - Dirgantara, Mohammad Videla Rosendy; Mawardi, Moh. Cholid; Rudhiningtyas, Dyah Arini (Universitas Islam Malang, 2025)
This study aims to analyze the effect of investment literacy, risk perception, and the influence of social media influencers on students’ investment interest at Universitas Islam Malang, as well as to examine the moderating role of influencers. This research employed a quantitative method, with data collected through questionnaires from 100 undergraduate students of Universitas Islam Malang selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS. The results indicate that investment literacy (X1) has a positive and significant effect on students’ investment interest, meaning that the higher the level of investment literacy, the greater the students’ tendency to invest. Risk perception (X2) also has a positive and significant effect, showing that students who are able to assess risks realistically are more confident in making investment decisions. The influencer variable in social media was found to play a moderating role, strengthening the relationship between investment literacy (X1) and investment interest, but weakening the relationship between risk perception (X2) and investment interest. These findings support the Theory of Planned Behavior (TPB), which emphasizes that perceived behavioral control, risk perception, and subjective norms influenced by social media influencers can encourage students to develop stronger intentions to invest.Keywords: Investment literacy, risk perception, influencer, investment interest.